Improving The Cost Performance of Mechanical Electrical And Plumbing (MEP) Works Buildings In Hotel Based on Building Information Modeling (BIM) 5D - Husin, Albert Eddy; Sihombing, Syamsir Abe; Kussumardianadewi, Bernadette Detty; Rahmawati, Diah Ika (CSID Journal of Infrastructure Development, 2020)
High-rise building projects expose a high risk due to structural design complexity, large workloads, and long project duration. The complexity of the work includes the design of Mechanical, Electrical, Plumbing (MEP), HVAC (Heating, Ventilation and Air Conditioning) systems, early warning, watering systems, hydrants, sprinklers, evacuation routes in the form of emergency stairs and fire doors. This research focuses on the application of BIM 5D to estimate and improve the cost performance of MEP work in high-rise hotel buildings. This research combines qualitative and quantitative approaches through in-depth interviews and BIM 5D modelling to achieve the research objective. The results showed influential factors for BIM implementation namely 2D Drawings, BIM 5D implementation, specification and technical plan, operator experiences, BIM 5D models, individual selection model, estimating, calculation process, cost database, and operator education. The findings of this research also show a cost efficiency of 3.56% from the BIM 5D implementation to the high-rise hotel building.